2005
DOI: 10.1007/s10681-005-5340-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal sampling strategies for evaluating fruit softening after harvest in apple breeding

Abstract: Environmental variance components associated with year, tree, and harvest date were estimated for fruit softening after harvest in apple (Malus × domestica Borkh.) to determine their relative importance and design optimum sampling strategies to discriminate genotypes in apple breeding. Fruit were stored after harvest under 20 ± 2 • C and 80 ± 5%RH. Softening was evaluated by adapting the change in firmness during storage to a linear regression and defining the regression coefficient as the softening rate. Envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…The lack of interaction could be attributed to the softening rates of individual progenies not being significantly different from year to year. This observation was consistent with the results of Iwanami et al (2005a), which showed that the softening rate, represented by a linear regression coefficient, was stable against environmental conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of interaction could be attributed to the softening rates of individual progenies not being significantly different from year to year. This observation was consistent with the results of Iwanami et al (2005a), which showed that the softening rate, represented by a linear regression coefficient, was stable against environmental conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The regression coefficient measures the softening rate and can be estimated from a limited number of harvested fruit in breeding situations. Iwanami et al (2005a) also indicated that, although the estimate of the parameter was influenced by environmental factors such as year, tree, and sampling date, the magnitudes of the influence were relatively small, and the estimate was considered to be stable against environmental conditions. The linear regression coefficient, therefore, can be a useful index for comparing relatives as the phenotypic value of softening after harvest.…”
mentioning
confidence: 99%
“…Iwanami et al [38] investigated 23 cultivars and a breeding line under a time-course experiment to evaluate firmness and mealiness and divided them into four groups based on their results after 40 days of storage at 20 • C. The watercore-susceptible cultivars 'Starking Delicious' and 'Red Gold' were placed in the most rapid mealiness developing group, whereas 'Fuji' was the firmest and most nonmealy cultivar. This was consistent with other previous studies [44][45][46]. Iwanami et al [47] also found that the softening performance of an apple cultivar during storage was highly dependent on the degree of mealiness and turgor reduction rate.…”
Section: Apple Cultivars and Texture Measurementsupporting
confidence: 92%
“…Because the degree of the change in firmness during storage can fluctuate depending on environmental factors such as harvest year (Ingle and Morris, 1989), orchard, and harvest date (Johnston et al, 2002b), the prediction of fruit quality after cold storage may not be accurate if each fruit under cold and shelf temperature is sampled under different environmental conditions. However, environmental variances of the firmness reduction rate such as those associated with genotype · year, year · tree, tree and harvest date were all reported to be very small by comparison with variance associated with genotype (Iwanami et al, 2005a). Therefore, the estimate of the effect of the storage The prediction was made by multiplying the days of storage at 20°C by 8.9 in each cultivar.…”
Section: Discussionmentioning
confidence: 99%